Analisis Efektivitas Penyaluran Dana Zakat Infak Shadaqah dan Implementasi Good Corporate Governance pada Lembaga Amil Zakat Dompet Dhuafa Waspada Medan - Annisa Zahara; Rahmi Syahriza; Yenni Samri Juliati Nasution (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study focuses on the effectiveness and capacity of Zakat, Infak, and Shadaqah (ZIS) fund distribution by Dompet Dhuafa Waspada and the implementation of Good Corporate Governance (GCG) principles. The researcher used a qualitative descriptive method. The data sources for this study were primary and secondary data, as well as literature studies. Data were collected through interviews, observations, and documentation. The analysis technique used data reduction, data display, and conclusion drawing methods. The effectiveness of ZIS fund distribution was measured using the Allocation to Collection Ratio (ACR) ratio based on the Zakat Core Principle (ZCP). The results show that Dompet Dhuafa Waspada has a very effective performance, with an average ACR reaching 90% in the last five years. In 2019, the ACR value was recorded at 87% in the effective category, in 2020, the ACR dropped to 71% in the effective category, then the ACR recovered to 74% in the effective category in 2021. At its peak, in 2022 and 2023, the ACR jumped to 106%. This shows a very good capacity in the management and distribution of ZIS funds that are right on target. The implementation of Good Corporate Governance is carried out through the principles of accountability, transparency, responsibility, independence, and equality, all of which increase public trust and the credibility of the institution. This study is expected to encourage more people to channel social funds through Dompet Dhuafa Waspada.